Assessment of awareness and attitude of rural women towards ill-effects of indoor air pollution and their perception regarding alternate cooking fuel usage in Mangalore - Alex, Prince; K. G., Kiran; Baisil, Sharon; A. U., Shameena; Badiger, Sanjeev (International Journal Of Community Medicine And Public Health, 2018)
Background: Indoor air pollution is typically underreported and less regulated than its counterpart. So this study was to assess the awareness and attitude of the study population towards ill effects of indoor smoke exposure among the study population and to assess the users’ perception about other alternative fuels to be used to reduce the ill effects. Objectives of the study were to assess the awareness and attitude of the study population towards ill effects of indoor smoke exposure among the study population and to assess the users’ perception about other alternative fuels to be used to reduce the ill effects. Methods: It was a cross- sectional study conducted in the rural field practice area of K.S Hegde Medical Academy among the household women who spend the majority time cooking in their house. The study included 400 household women. Data was collected using a pre-tested, semi-structured questionnaire, and entered into MS Excel and analysed. Results: Most (80.8%) of them were aware that exposure to smoke affects the health of those exposed to it. Also, their perception regarding alternate fuels was good. In the study most of the study participants (92.1%) were willing to change over to a cleaner fuel. Conclusions: By raising their awareness towards the harmful effects of firewood smoke and providing awareness regarding government programmes for using cleaner fuels, the ill-effects on health of those involved in cooking can be reduced in future.